Transforming the European Legal Order: The European Court of Justice at 60+ - Jessica Guth (Journal of Contemporary European Research, 2016)
The European Court of Justice has played a pivotal role in the transformation of international law obligations between Member States into an integrated legal order with direct applicability and effect in those Member States. This article explores whether or not the ECJ continues to be relevant to EU governance and integration and whether it continues to transform the legal orders of the Member States. It briefly outlines the early case law which transformed the legal order, and the preliminary reference procedure as an important element of that transformation, and then considers the extent to which the ECJ continues to act in ways which are transformational even though the legal order itself has remained relatively static. The EU citizenship jurisprudence serves as a useful example of how integration is driven forward by the Court. This article argues that the Court’s decisions do continue to have significant impact on areas of law and policy and EU governance generally. It illustrates this argument using gender equality law and Human Rights as pertinent examples and concludes that the ECJ remains relevant in governance terms as it continues to drive forward EU integration in many areas and influence the development of law and policy across the Member States.